Inequality and globalization: Improving measurement through integrated financial accounts - Paweenawat, Archawa; Townsend, Robert M. (New Jersey Princeton University Press, 2024)
Increasing inequality, the impact of globalization, and the disparate effects of financial regulation and innovation are extraordinarily important topics that fuel spirited policy debates. And yet the facts underlying these debates are of doubtful accuracy. In reality, as Archawa Paweenawat and Robert Townsend show in Inequality and Globalization, there is a large gap between micro household surveys, which measure key outcomes such as inequality, and aggregated financial accounts, which measure macroeconomic totals and growth.